Risk and expected returns of private equity investments: Evidence based on market prices - Narasimhan Jegadeesh; Roman Kräussl; Joshua Pollet (Goethe University Frankfurt, Center for Financial Studies (CFS), 2010)
We estimate the risk and expected returns of private equity investments based on the market prices of exchange traded funds of funds that invest in unlisted private equity funds. Our results indicate that the market expects unlisted private equity funds to earn abnormal returns of about one to two percent. We also find that the market expects listed private equity funds to earn zero to marginally negative abnormal returns net of fees. Both listed and unlisted private equity funds have market betas close to one and positive factor loadings on the Fama-French SMB factor. Private equity fund returns are positively correlated with GDP growth and negatively correlated with the credit spread. Finally, we find that market returns of exchange traded funds of funds and listed private equity funds predict changes in self-reported book values of unlisted private equity funds.
urn:nbn:de:hebis:30-75150
Keywords: G12; 330; Private Equity; Listed Private Equity; Risk-Return Characteristics; Funds of Funds; Kapitalanlage; Private Equity; Kapitalertrag; Risiko; Welt